The reform of vocational education and training in Bulgaria: the impact of recent innovations in teaching and learning - Smith, Christopher J. (2003)
Much has been written over recent years questioning the value of exporting systems of VET from developed countries and expecting them to meet the needs and demands of developing countries. Most recently, the main recipients of development aid, particularly from the EU, have been the countries of the former 'eastern bloc'. As a consultant working on an EU project to upgrade VET in Bulgaria, the author was involved in delivering staff development seminars concentrating on 'new' teaching and learning strategies to teachers within the secondary vocational sector. Although the staff development was well received at the time, questions were raised about whether such fundamental changes in approach, from a very authoritarian and didactic approach, to an approach that is student-centred, could be sustained on the basis of a series of seminars. This thesis examines what impact these seminars have had in promoting the use of the 'new' strategies. In particular, the author examines to what extent cultural and / or contextual factors have played a role in the effectiveness of implementation of the 'new' student-centred teaching and learning strategies.